The Influence of Life Quality to The House Physical Change in Perum Griya Praja Mukti Kendal - Mahardini, Irnita (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The quality of physical improvement of houses usually reflects the quality of life of the owner. The need for selfâ€actualization often triggered physical changes in the houses diverse in form and range depending on the ability, desire and needs of the family. The uncontrolled physical developments of house constructions, particularly in the Simple House (Rumah Sederhana â€“ RS) and Very Simple House (Rumah Sangat Sederhana â€“ RSS) range has been indicated to cause environmental damage, demanding further attention. The study examined Griya Praja Mukti RSS Housing in Kendal District, involving 83 households in the area. Quantitative approach were employed using using questionnaires, accompanied by interviews and observations. The study exercised cross tabulation, Chi square analysis, double regression and contingency coefficient correlation Analysis to verify the link among the variables. The study has confirmed the link between the level of physical changes of the construction of the houses to the quality of life of the inhabitant i.e. the economic and social condition.